A Fast Settling, 0.1-100% Duty-cycled, 1-100 mA Accurate Current Control LED Driver for PPG Sensor System - Lim, Sung Won; Jee, Dong Woo (Journal of Semiconductor Technology and Science, 2024)
A wide operating range, fast settling, and accurate current sourcing LED driver for PPG (Photoplethysmography) sensor applications is presented. Proposed NMOS resistor array and RC-time constant based calibration circuit precisely control target LED driving current with less than 0.5% error over process variations. For the fast settling of pulse-width modulation (PWM) based boost converter loop, pulse-width prediction technique is proposed which greatly improves the settling time. The driver circuit is designed in 180-nm CMOS process, supporting green/red/infrared LED driving voltage, 0.1-100% duty-cycling and 1-100 mA driving current.
Keywords: 'current; BOOST converter; Current calibration; Driving current; Fact settling; LED drivers; Operating ranges; Photoplethysmography sensor; Sensor applications; Sensor systems; boost converter; current calibration; fact settling; LED driver; PPG sensor